Towards an Integration of UBI and Its Clusters’ Capabilities with IOA (Internet of Agents): A First Step and a Roadmap - Taiwo, Ademola (Global journal of Business and Integral Security, 2026)
The emergence of Agentic AI and AI Agents has proliferated the use of automation in enterprise processes. UBI as a community and ecosystem must also tap into this opportunity and trends of AI agents as a Service usage and context protocols via the integration of needed AI Agents and accompanying technologies like IoA into their business workflows. The advent of Internet of Agents(IoA) will also spur the interconnection of different agents (virtual and embodied robots) across enterprise and institutions using newly established communication protocols like A2A, ANP, ACP and AGNTCY. This study presents an introductory first step on how UBIs and their clusters can securely integrate their processes with Agents Communication Protocols like A2A, function calling and resource access like MCP and IoA (Internet of Agents) while also extending the application and integration across several industries and clusters such as MedTech, Biotech, Nanotech, Fintech, Network of UBIs, Luxury, Space Based Business Incubation Centers and Insurance. The proposed introductory steps and roadmap will ensure future interconnected private networks of UBI Agents across different UBI domains and multi-operability of Agents with secure knowledge flows and knowledge bases.